2016
DOI: 10.1136/jclinpath-2016-203951
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Singapore nomogram for outcome prediction in breast phyllodes tumours: an Australian cohort

Abstract: The Singapore nomogram is useful in predicting outcome in breast phyllodes tumours when applied to an Australian cohort of 34 women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Chng et al suggested even not to reexcise borderline PT with positive surgical margins due to the absence of LR in their sample. However, their study was not representative enough as included only 7 cases with a short median follow-up of 20.4 months [38]. Our meta-analysis results support that the common practice of a 10 mm margin shows a clear reduction in rates of LR for borderline PT.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Chng et al suggested even not to reexcise borderline PT with positive surgical margins due to the absence of LR in their sample. However, their study was not representative enough as included only 7 cases with a short median follow-up of 20.4 months [38]. Our meta-analysis results support that the common practice of a 10 mm margin shows a clear reduction in rates of LR for borderline PT.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, some authors reported no increase of LR when the PT lesion was in contact with surgical margins [58]. Even further, other authors suggested no immediate re-excision and only a follow-up for benign PT when the surgical resection was in positive margins [6,38,64,65]. Our findings contest this advice, as we found that for benign PT the LR rate was 5.22 per 100 person-years with margins narrower than 10 mm and only 3.63 with margins at least 10 mm (i.e., a decrease of 30% of LR rate), over a 5-year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This nomogram was subsequently validated in two small case series [35,36]. Its widespread use in clinical practice is limited by the rarity of PTs in general.…”
Section: Factors Associated With Metastasismentioning
confidence: 99%
“…These results again reflect difficulties in applying subjective criteria on a small amount of tissue, but also in applying them on potentially non-representative sampling of a tumour type that is often heterogeneous 15. And while it was reassuring that moderate digital point counting correlations between core and excision were observed, these might have been stronger if not for the established fact that FAs can have areas resembling PT and vice versa 15…”
Section: Discussionmentioning
confidence: 99%